Sphingosine‐1‐phosphate phosphatase 2 promotes disruption of mucosal integrity, and contributes to ulcerative colitis in mice and humans. Issue 8 (29th April 2016) - Huang, Wei‐Ching; Liang, Jie; Nagahashi, Masayuki; Avni, Dorit; Yamada, Akimitsu; Maceyka, Michael; Wolen, Aaron R.; Kordula, Tomasz; Milstien, Sheldon; Takabe, Kazuaki; Oravecz, Tamas; Spiegel, Sarah
ABSTRACT: The bioactive sphingolipid sphingosine‐1‐phosphate (S1P) and the kinase that produces it have been implicated in inflammatory bowel diseases in mice and humans; however, little is known about the role of the 2 S1P‐specific phosphohydrolase isoforms, SGPP1 and SGPP2, which catalyze dephosphorylation of S1P to sphingosine. To elucidate their functions, we generated specific knockout mice. Deletion of Sgpp2, which is mainly expressed in the gastrointestinal tract, significantly reduced dextran sodium sulfate (DSS)‐induced colitis severity, whereas deletion of ubiquitously expressed Sgpp1 slightly worsened colitis. Moreover, Sgpp1 deletion enhanced expression of multifunctional proinflammatory cytokines, IL‐6, TNF‐α, and IL‐1β, activation of the transcription factor signal transducer and activator of transcription 3, and immune cell infiltration into the colon. Conversely, Sgpp2‐null mice failed to mount a DSS‐induced systemic inflammatory response. Of interest, Sgpp2 deficiency suppressed DSS‐induced intestinal epithelial cell apoptosis and improved mucosal barrier integrity. Furthermore, down‐regulation of Sgpp2 attenuated LPS‐induced paracellular permeability in cultured cells and enhanced expression of the adherens junction protein E‐cadherin. Finally, in patients with ulcerative colitis, SGPP2 expression was elevated in colitis tissues relative to that in uninvolved tissues. These results indicate that induction of SGPP2 expression contributes to the pathogenesis of colitis by promoting disruption of the mucosal barrier function. SGPP2 may represent a novel therapeutic target in inflammatory bowel disease.—Huang, W.‐C., Liang, J., Nagahashi, M., Avni, D., Yamada, A., Maceyka, M., Wolen, A. R., Kordula, T., Milstien, S., Takabe, K., Oravecz, T., Spiegel, S. Sphingosine‐1‐phosphate phosphatase 2 promotes disruption of mucosal integrity, and contributes to ulcerative colitis in mice and humans. FASEB J. 30, 2945‐2958 (2016). www.fasebj.org